Pengaruh Struktur Modal, Pertumbuhan Penjualan, Ukuran Perusahaan Terhadap Profitabilitas (Pada Perusahaan Pembiayaan yang Terdaftar di BEI Periode 2018-2023) - Farli Jibalmi; Tri Rachmat Riski (GLOBAL SCIENTS PUBLISHER, 2025)
The purpose of this study was to determine the effect of capital structure, sales growth and company size on the profitability (Study of financing companies listed on the Indonesia Stock Exchange (IDX) Period 2018 - 2023). This study takes a sample of financing companies listed on the Indonesia Stock Exchange (IDX) whose financial statements have been audited. The research data of 13 companies and obtained a sample of 10 companies. The data analysis method used is multiple linear regression with a significance level of 0.05. The results of this study indicate that capital structure has a positive and significant effect on company profitability, sales growth has a positive and significant effect on company profitability and company size partially has a negative and significant effect on company profitability.